Effects of anti-CD4 antibody treatment on calcium ions influx in peanut-sensitized C3H/HeJ mice - Junjuan Wang; Cui Zhou; Shiwen Han; Zainabu Majid; Na Sun; Huilian Che (Food Science and Human Wellness)
The precise mechanism underlying the effects of anti-CD4 antibody and calcium ions (Ca2+) in peanut allergy remains unknown. C3H/HeJ mice sensitized with peanut protein extract (PPE) were injected with anti-CD4 antibodies for 4 weeks. Stimulation with PPE increased the specific immunoglobulin (IgE), cytokine, histamine, and mMcp-1 levels, upregulated decorin (Dcn) expression, induced Ca2+ inflow in the spleen, and augmented the expression of the transcription factors GATA-3 and Foxp3, which resulted in Th2 and Treg cell activation. Notably, the Ca2+ levels were positively correlated with the histamine, interleukin (IL)-4, IL-5, and IL-13 levels, and negatively correlated with IL-10 levels. However, administration of anti-CD4 antibodies markedly alleviated allergic symptoms, activated T cells, and reduced Ca2+ inflow, cytokine, histamine, mMcp-1, and the IgHG3, CXCL12, MMP2 and FABP4 gene. Our results indicated that anti-CD4 antibodies can ameliorate PPE-induced allergy, which is probably related to the suppression of Ca2+ inflow, and inhibiting histamine, cytokine and IgHG3, CXCL12, MMP2, and FABP4, thus exerting a protective effect against PPE-sensitized food allergy.